2020
DOI: 10.5539/ies.v14n1p76
|View full text |Cite
|
Sign up to set email alerts
|

Educational Research Training in Teacher Training Programs: The Views of Future Teachers

Abstract: The objectives of this study were to explore teacher student’s views on the research training they receive and know their suggestions for improving it. This was a qualitative study conducted on students in the teacher training programs of a Chilean public university who were distributed into nine focus groups. The findings showed that the students have a rather critical view about the training they receive, particularly due to the lack of continuity of research-related courses and their limited parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
(33 reference statements)
1
7
0
6
Order By: Relevance
“…This section presents the results of the analysis of the teachers' responses regarding their use of multimodality in teaching and their awareness, perception, and experiences of multimodality before and during the COVID-19 period (Perines, 2021). It also presents findings on the teachers' use of technology in line with multimodality before and during the COVID-19 period, as well as on the opinions of the teachers regarding their students' perceptions and interactions with multimodality and the challenges of using multimodality in teaching during the COVID-19 period.…”
Section: Multimodality Analysismentioning
confidence: 99%
“…This section presents the results of the analysis of the teachers' responses regarding their use of multimodality in teaching and their awareness, perception, and experiences of multimodality before and during the COVID-19 period (Perines, 2021). It also presents findings on the teachers' use of technology in line with multimodality before and during the COVID-19 period, as well as on the opinions of the teachers regarding their students' perceptions and interactions with multimodality and the challenges of using multimodality in teaching during the COVID-19 period.…”
Section: Multimodality Analysismentioning
confidence: 99%
“…2) PEB conceptualiza el proceso de práctica pedagógica como una instancia para desarrollar habilidades procedimentales, lo que se puede atribuir al enfoque didáctico que se plantea en el Perfil de Egreso de profesores de Educación General Básica, que se alinea con los estándares para dicho programa (Ministerio de Educación de Chile, 2012). No obstante, en la formación profesional no se debería establecer una distancia entre teoría y práctica, sino diversificar las instancias integrales para acercar a los PF a la reflexión e investigación (Perines, 2021). Es importante señalar que, en la formación de profesores, especialmente de primaria, no debe perderse de vista el desarrollo de las habilidades socioemocionales, el rol del cuidado y de la pedagogía de los sentimientos en la relación profesor y niños (O'Connor et al, 2020), particularmente en el contexto actual.…”
Section: De Los Propósitos De Las Prácticasunclassified
“…Most studies indicate that many research-based courses have been embedded in the initial teacher education curriculum both in different forms and at different stages in several countries worldwide (e.g. Pesti et al, 2018;Perines, 2020;Smith, 2015;Katwijk et al, 2021). After the implementation of these research-based courses in teacher education programs, the promising accomplishments of the graduates in research have been observed.…”
Section: Research In Pre-service Teacher Educationmentioning
confidence: 99%
“…This growing need stimulates some studies exploring PSTs' views on research and/or research-based courses and their way of becoming research literate in diverse settings (e.g. Banegas, 2018;Cain & Allan, 2017;Elmas and Aydin, 2017;Perines, 2020;Roberts & Allen, 2013;Spronken-Smith, 2014;Katwijk, Berry, Jansen & van Veen , 2019;van der Linden, Bakx, Ros, Beijaard & Vermeulen, 2012;van der Linden, Bakx, Ros, Beijaard & van den Bergh, 2015) although these studies are meager in quantity. To map out the standpoint of pre-service teachers in the relevant network, the theoretical framework will be hereafter organized in two main headings, which are the most relevant themes described in the related domain, to explain: primarily 'teacher as a researcher' notion through the prevailing literature and followingly how research is embedded in teacher education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation